A review of the efficiency of discharge plasma and algae for wastewater treatment - Bahareh Nowruzi; Nedasadat SafarabadiFarahani; Mohammad Jabari (رویکردهای نوین در مهندسی آب و محیط زیست)
Owing to the water crisis, the development of innovative and clean advanced oxidation processes to decompose a variety of harmful organic compounds in wastewater has become the main challenge for many research teams. In fact, continuous increasing concentrations of antibiotics in the environment is a serious potential hazard due to their toxicity and persistence. Unfortunately, conventional treatment techniques, such as those utilized in wastewater treatment plants, are not efficient for the treatment of wastewater containing antibiotics. Recently, technologies based on algae as well as cold discharge plasma are among the processes that have been widely studied and developed due to their low energy cost and easy operation. In this review article, the mechanisms of bioabsorption, bioaccumulation and biodegradation using algae-bacteria consortia to remove antibiotics, the integration of algae with other microorganisms, and the effect of various factors on the effectiveness of decontamination by discharge plasma have been investigated. In addition, the production and reaction mechanisms of active compounds in discharge plasma systems, the potential and design of the laboratory-scale reactor, the combination of discharge plasma for decontamination with other processes, post- and pre-treatment along with the use of algae as a precursor for the production and modification of biochar With other materials to improve the removal capacity of a more attention hass in algae-mediated antibiotic removal technologies with cold plasma and provides insights for reducing waste consumption in aquatic environments.